Analisis Pertimbangan Hukum Terkait Pelanggaran Hak Cipta “Urban Light” (Studi Putusan No 31/Pdt.Sus-Hak Cipta/2020/Pn.Niaga.Jkt.Pst) - Raudah, Bunga; Saidin; Sitepu, Faradila Yulistari (Talenta Publisher, Universitas Sumatera Utara, 2025)
This study aims to analyze the legal considerations related to copyright infringement in the case of